A Study of Anxiety Disorders in Terms of Severity and Prevalence in Patients of Major Depressive Disorder in a Tertiary Care Centre - Rani, Dr Richa; Bala, Neeru; Garg, Parshotam Dass; Bansal, Aashish (International Journal of Innovative Research in Medical Science, 2018)
Background: Depression is a disorder of major public health importance. Over the last 50 years, large number of studies have been published from India addressing various aspects of depression. The objective of the current study was to study the socio-demographic characteristics and anxiety as co-morbidity in patients with major depressive disorder. Method: This was a cross sectional study conducted in tertiary care hospital in which 100 patients diagnosed with major depressive disorder, according to ICD-10 were assessed for presence of anxiety disorder as psychiatric Comorbidity using MINI and severity of anxiety was assessed using HAM-A. Results: Current study showed major depressive disorder is more common among females 59%, married 79%, housewife 50%, 61% had first episode of depression and 27% had family history of major depressive disorder. There was 48% presence of any anxiety disorder among total major depressive disorder patients. Among which 25% had generalized anxiety disorder, 9% obsessive compulsive disorder, 5% panic disorder, 4% agoraphobia, 4% post traumatic stress disorder and 1% social anxiety disorder among total patients with major depressive disorder. The maximum number of patients 43% had mild to moderate level of anxiety, 32% had mild anxiety, 19% had moderate to severe anxiety and 6% had severe anxiety. Conclusion: There is a high prevalence of anxiety disorders in major depressive disorder which is oftenly ignored because of symptom overlap between anxiety and major depression. This study is important because of increasing prevalence of psychiatric comorbidity among the patients of major depressive disorders lead to impaired functioning in patients with MDD. Therefore, monitoring of symptoms as well as functioning during the long-term management MDD could be crucial to achieve the functioning remission.